Inhibiting Histone Deacetylase 2 (HDAC2) Promotes Functional Recovery From Stroke - Ying Tang; Yu‐Hui Lin; Huanyu Ni; Jian Dong; Hong‐Jin Yuan; Yu Zhang; Haiying Liang; Mengcheng Yao; Qi‐Gang Zhou; Hai‐Yin Wu; Lei Chang; Chun‐Xia Luo; et al. (2017)
Background Stroke is a leading cause of long‐term disability worldwide. However, current therapies that promote functional recovery from stroke are limited to physical rehabilitation. No pharmacological therapy is available. Thus, understanding the role of histone deacetylase 2 (HDAC2) in the pathophysiological process of stroke‐induced functional loss may provide a novel strategy for stroke recovery. Methods and Results Focal stroke was induced by photothrombosis. LV‐HDAC2‐shRNA‐GFP, LV‐GFP, Ad‐HDAC2‐Flag, or Ad‐inactive‐HDAC2‐Flag was microinjected into the peri‐infarct area immediately after stroke. HDAC inhibitors were microinjected into the peri‐infarct area 4 to 10 days after stroke. Grid‐walking task and cylinder task were conducted to assess motor function. Golgi‐Cox staining, chromatin immunoprecipitation, and electrophysiology were used to reveal the mechanisms underlying stroke recovery. Knockdown or knockout of HDAC2 promoted stroke recovery, whereas overexpression of HDAC2 worsened stroke‐induced functional impairment. More importantly, trichostatin A, a pan‐HDAC inhibitor, promoted functional recovery from stroke in WT mice when used in the delayed phase, but it was ineffective in Hdac2 conditional knockout ( Hdac2 CKO) mice. Treatment with suberoylanilide hydroxamic acid, a selective HDAC1 and HDAC2 inhibitor, in the delayed phase of stroke produced sustained functional recovery in mice via epigenetically enhancing neuroplasticity of surviving neurons in the peri‐infarct zone. Conclusions Our novel findings provide evidence that HDAC2 is a crucial target for functional recovery from stroke. As there are clinically available HDAC inhibitors, our findings could be directly translated into clinical research of stroke.